Revisiting the taxonomy of Rhabdias fuelleborni Travassos, 1928 (Nematoda, Rhabdiasidae) with approaches to delimitation of species and notes on molecular phylogeny - Müller, Maria Isabel [UNESP]; Morais, Drausio Honorio; da Costa, Lorena Freitas Souza Tavares; de Vasconcelos Melo, Francisco Tiago; Giese, Elane Guerreiro; Ávila, Robson Waldemar; da Silva, Reinaldo José [UNESP] (Elsevier, 2023)
Rhabdias fuelleborni was described by Travassos (1926), who identified it in the lungs of Rhinella gr. marina (=Bufo marinus) from São Paulo. Later, Kloss (1971) added new information on the morphology and diagnosis of the species and new data on host and localities. However, its taxonomic status remains uncertain, due in particular to the morphological uniformity of Rhabdias spp., while the original description lacks important morphological data. In the present study, we found and reevaluated the type series of R. fuelleborni, as well as examining fresh material obtained from the type host and type locality, using light and scanning electron microscopy and molecular tools. The type series was deposited by Travassos (1926), and according to museum records the type locality is Paraty, Rio de Janeiro, Brazil. Our morphological and molecular analyses reinforce the taxonomic validity of this species, while molecular phylogeny identified a close relationship between R. fuelleborni and Rhabdias sp.4 and Rhabdias sp. from other studies, and from bufonids. Also R. fuelleborni are sister taxa with R. cf. stenocephala from Leptodactylidae from the northeast of Brazil and R. vencesi from Boophis madagascarariensis, Madagascar, according to mitochondrial COI gene.
Keywords: Amphibians; Bufonidae; COI; Neotropical realm; Ribosomal genes